Surveillance for subsequent neoplasms of the CNS for childhood, adolescent, and young adult cancer survivors: a systematic review and recommendations from the International Late Effects of Childhood Cancer Guideline Harmonization Group. Issue 5 (May 2021) - Bowers, Daniel C; Verbruggen, Lisanne C; Kremer, Leontien C M; Hudson, Melissa M; Skinner, Roderick; Constine, Louis S; Sabin, Noah D; Bhangoo, Ranjeev; Haupt, Riccardo; Hawkins, Mike M; Jenkinson, Helen; Khan, Raja B; et al.
Summary: Exposure to cranial radiotherapy is associated with an increased risk of subsequent CNS neoplasms among childhood, adolescent, and young adult (CAYA) cancer survivors. Surveillance for subsequent neoplasms can translate into early diagnoses and interventions that could improve cancer survivors' health and quality of life. The practice guideline presented here by the International Late Effects of Childhood Cancer Guideline Harmonization Group was developed with an evidence-based method that entailed the gathering and appraisal of published evidence associated with subsequent CNS neoplasms among CAYA cancer survivors. The preparation of these guidelines showed a paucity of high-quality evidence and highlighted the need for additional research to inform survivorship care. The recommendations are based on careful consideration of the evidence supporting the benefits, risks, and harms of the surveillance interventions, clinical judgment regarding individual patient circumstances, and the need to maintain flexibility of application across different health-care systems. Currently, there is insufficient evidence to establish whether early detection of subsequent CNS neoplasms reduces morbidity and mortality, and therefore no recommendation can be formulated for or against routine MRI surveillance. The decision to start surveillance should be made by the CAYA cancer survivor and health-care provider after careful consideration of the potential harms and benefits of surveillance for CNS neoplasms, including meningioma.